A Typology of Scientific Advisory Committees - Gaëlle M. N. Groux; Steven J. Hoffman; Trygve Ottersen (Global Challenges, 2018)
Abstract The era of evidence‐informed decision‐making has seen increased use of the scientific advisory committee (SAC) to provide decision‐makers with scientific advice, despite limited evidence of the effectiveness or best strategies for designing these committees. In this study, an in‐depth review of academic and gray literature is undertaken to outline the global landscape of SACs. The development of a typology is also undertaken that categorizes SACs along six dimensions: 1) sector, 2) level of operation, 3) permanence, 4) target audience, 5) autonomy, and 6) nature of advice. It is found that SACs differ profoundly in each of these dimensions and provide examples demonstrating this variation. The landscape and typology can help decision‐makers understand the key elements of SAC design and reform, and the results will also inform future research on the design and effectiveness of SACs. With SACs expected to promote evidence‐informed decision‐making, it is imperative that the design of these committees themselves is guided by evidence.